Aplikasi Teknik Identifikasi Organisme Pengganggu Tanaman dan Teknologi Pembuatan Biopestisida sebagai Upaya Pemanfaatan Tanaman Sekitar dan Produksi Pertanian yang Berkelanjutan - Noor Rahmawati; Mustika Dewi; Mamat Kandar (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Sustainable agriculture always utilises natural materials and avoids the use of synthetic materials in an effort to increase agricultural production, without damaging the environment. Understanding the meaning of sustainable agriculture to farmers is still not much done. Farmers of Cinanjung village, Tanjungsari sub-district, Sumedang Regency, are conventional horticultural farmers who mostly do not understand the concept of sustainable agriculture so that there are still many farmers who use synthetic fertilisers and synthetic pesticides in an effort to increase their production, without realising that it can harm the environment. The SITH ITB Community Service Team tried to provide an understanding of the importance of sustainable agriculture and training in the identification of plant pest organisms (OPT) and the production of biopesticides from surrounding plants, so that they could support the programme. The results of the Community Service Activities show that the existence of this community service programme is able to increase knowledge and understanding of sustainable agriculture and the skills of identification of plant pest organisms and biopesticide production skills from microbial resources and surrounding plants